2006
DOI: 10.1097/01.jom.0000225137.19863.4e
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and Lung Cancer Mortality in a Nationally Representative U.S. Cohort: The National Health Interview Survey (NHIS)

Abstract: Although tobacco use continues to be the single most important risk factor for lung cancer mortality, occupational exposure to lung carcinogens should be targeted as well to further reduce the burden of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…A body of literature supports our findings (Aronson et al 2000;Bruske-Hohlfeld et al 2000;Chen et al 1995;Kreuzer et al 2000;Lee et al 2006;NIOSH 2003;Reger and Morgan 1993;Siemiatycki 1991). Exposure to dust (containing silica, inorganic acid mists, etc.)…”
Section: Mining and Metallurgical Worksupporting
confidence: 91%
See 1 more Smart Citation
“…A body of literature supports our findings (Aronson et al 2000;Bruske-Hohlfeld et al 2000;Chen et al 1995;Kreuzer et al 2000;Lee et al 2006;NIOSH 2003;Reger and Morgan 1993;Siemiatycki 1991). Exposure to dust (containing silica, inorganic acid mists, etc.)…”
Section: Mining and Metallurgical Worksupporting
confidence: 91%
“…They share some common exposures, including formaldehyde and medical radiation, both of which are associated with an increased risk of lung cancer (IARC 2000(IARC , 2006Siemiatycki et al 2004). Although there is evidence of protective or null effect (Aronson et al 2000;Blair, Walrath, and Rogot 1985;Bruske-Hohlfeld et al 2000;Burns and Swanson 1991;Jockel et al 1998;Lee et al 2006;NIOSH 2003;Zahm et al 1989), an elevated risk found in another Canadian study (Siemiatycki 1991) supports further investigation.…”
Section: Construction Workmentioning
confidence: 82%
“…Epidemiological studies on populations exposed to PAH mixtures have shown a link between these exposures, and cancers of the lung, respiratory system, and stomach (Bertrand et al, 1987;Puisieux et al, 1991;Krewski and Thomas, 1992;Vyskocil et al, 2004). Smoking and exposure to environmental tobacco smoke (ETS) have been shown to be associated with cancer in the lung, bronchus, larynx, bladder, cervix, and oral mucosa (Phillips, 1997;Lee et al, 2006;Yach and Wipfli, 2006). PAH exposure levels are classically estimated by air sampling.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard environmental tobacco exposure has now become an important labor issue, and the promotion of smoke-free surroundings comprises an essential component of any healthy and safe modern workplace 11) . While tobacco use remains the single most preventable cause of lung cancer 12) , contemporary reductions in lung cancer rates appear to have been preceded by a reduction in community smoking habits during the latter half of last century 13) . Quitting clearly offers major benefits for smokers, with Doll and colleagues 14) showing that British physicians who quit by age 50 were able to reduce their smoking-related hazard by almost half.…”
Section: Introductionmentioning
confidence: 99%